Pusat Keseimbangan Ciptaan: Kritik Retorik terhadap Peran La’abod Manusia dalam Ekologi Mazmur 104:14-23 - David Martin Doli Sitorus (PASCA : Jurnal Teologi dan Pendidikan Agama Kristen, 2026)
This study analyzed Psalm 104:14-23 using rhetorical criticism and semantic analysis, focusing on the concept of human la’abod within the context of creation ecology. Psalm 104 depicted a harmonious world in which humans, animals, plants, and the environment operated within a rhythm established and sustained by God. Verses 14-23 occupied a central position in a concentric structure, emphasizing the balance of creation and the role of humans as participants rather than rulers. Semantic analysis of the term la’abod highlighted that human activities cultivating the land, processing agricultural produce, and working did not signify domination over creation but reflected participation in God’s ongoing sustenance. These findings had theological and ecological implications, promoting the transformation of faith awareness into concrete actions to care for the environment while rejecting anthropocentric views. Psalm 104 presented a theological vision that positioned humans within the ecological balance of creation, as a responsibility continuously upheld under God’s providence.